Community takes initiative - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The communities of the wetland and catchment area of Lake Chilwa, Malawi s second biggest lake and largest producer of fish, are engaged in a community based project to conserve the ecosystem of this inland drainage lake which dried up in 1997. In...